2011
DOI: 10.1111/j.1755-3768.2009.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complement factor H Y402H, LOC387715, HTRA1 polymorphisms and ApoE alleles with susceptibility to age‐related macular degeneration in Hungarian patients

Abstract: ABSTRACT.Purpose: Recent studies strongly support the role of genetic factors in the aetiology of age-related macular degeneration (AMD). We investigated the frequency of Tyr402His polymorphism of the complement factor H (CFH) gene, Ser69Ala polymorphism at LOC387715, rs11200638 polymorphism of the HTRA1 gene and different apolipoprotein E (ApoE) alleles in Hungarian patients with AMD in order to determine the disease risk conferred by these factors. Methods: In a case-control study, we performed clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
9
1
Order By: Relevance
“…Although the E2 allele is considered a risk allele (16) , no difference in risk was observed between the two groups. This finding is in accordance with that of other studies (14,15) . The protective nature of apoE4 can be explained by the lack of cysteine residues at positions 112 and 158, in contrast to apoE2 and apoE3.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although the E2 allele is considered a risk allele (16) , no difference in risk was observed between the two groups. This finding is in accordance with that of other studies (14,15) . The protective nature of apoE4 can be explained by the lack of cysteine residues at positions 112 and 158, in contrast to apoE2 and apoE3.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, similar to other studies (14,15) , an association of APOEHhaI polymorphism with AMD could not be confirmed, which is in contrast to another study (16) . The E3E3 genotype and E3 allele were pre valent in patients and controls, as observed in another study (7) .…”
Section: Discussioncontrasting
confidence: 55%
“…Previously we could not demonstrate statistically significant association between ApoE alleles and AMD in a Hungarian population. However, the potential risk factor E2 allele was less frequent in patients than in controls (0.066 and 0.1, respectively) while the E4 allele was more frequent in the patient group than in controls (0.108 versus 0.084, respectively), interestingly [32]. The somewhat inconsistent findings on the association of AMD and ApoE called for a recently published pooled analysis (n = 21.160) demonstrating that the E2 allele in homozygous form confers risk (OR = 1.83, 95%CI: 1.04–3.23) and the E4 allele is protective (OR = 0.72 per haplotype; 95%CI: 0.65–0.74) in late AMD [33].…”
Section: Introductionmentioning
confidence: 84%
“…Molecular genetic methods for the detection of the common ApoE alleles, CFH p.Tyr402His polymorphism, LOC387715 rs10490924 (p.A69S) and HTRA1 rs11200638 polymorphisms were used as described earlier [32]. Factor XIII Val34Leu polymorphism was detected using fluorescent PCR and hybridization probes [47].…”
Section: Methodsmentioning
confidence: 99%
“…These results have been replicated in other studies [112,113,114,115,116,117,118,119,120,121,122] and confirmed by a meta-analysis [123]. However, likely because of the weak allele effects of Apo-ε, and because of the low allele frequencies of both the ε2 and ε4 alleles, some studies could not demonstrate any association between this gene and AMD [124,125,126,127,128,129]. The ε4 allele is associated with a reduced risk of developing different subtypes of the disease (exudative or atrophic forms) [115,116], with sometimes a gender-specific protective effect reported for men [117], whereas a gender effect of the ε2 isoform might confer an increased risk mainly for men [115].…”
Section: Genetic Factors Associated With Amdmentioning
confidence: 99%